National legislative systems and foreign standards and regulations: The case of International Financial Reporting Standards adoption - Dima, Bogdan; Dima (Cristea), Stefana Maria; Moldovan, Nicoleta; Pirtea, Marilen Gabriel (MPRA Paper, 2010)
This study is focused on the linkages between the legislative families as descriptors of national legislative systems and International Financial Reporting Standards (IFRSs) issued by the International Accounting Standards Board (IASB). We consider such analysis as a case study for the more general issue of explaining the preferences of national regulators in the adoption of foreign norms, rules, standards and practices. By using a dataset of 162 jurisdictions and dummy variables designed to capture the current stage of IFRSs adoption and, respectively, the taxonomy of their legislative systems, we find that a full IFRSs adoption is more likely to occur in countries which have principles-based on legislative mono-systems. In addition, we observe that a strong rule of law, with an effective mechanism of property rights reinforcement, as well as the pre-adoption existence of a pro-growth set of public policies can contribute to the encouragement of IFRSs adoption.
Keywords: IFRSs adoption; Legislative families

The suitability of the South African corporate tax regime for the use of South African resident intermediary holding companies - Legwaila, Thabo (University of Pretoria, 2010)
An Intermediary Holding Company (“IHC”) is a company that is interposed between an ultimate holding company and the operating subsidiaries of a group of companies. The IHC operates at an international level such that either its holding company or its subsidiaries or both are located in a country foreign to the IHC. Its main functions are to acquire, manage and dispose of the assets of the group of companies and to facilitate structural flexibility of a group of companies. Investors have tax and non-tax reasons for conducting business using an IHC, and, depending on the reasons, they determine the location of the IHC based on the characteristics of potential host countries. This thesis analyses the suitability of the South African corporate tax regime for the use of South African-resident Intermediary Holding Companies. The South African government has the objective of promoting South Africa as a gateway for investment in Africa and for this reason the present research is important. Such an objective could be adversely affected by a corporate tax regime that is not suitable for the operations of an IHC. Furthermore, the Katz Commission recommended in 1997 that South Africa should consider introducing a regime that is suitable for the location of holding companies. In discharging its functions the IHC attracts liability for corporate income tax, capital gains tax, controlled foreign company tax and dividends tax. It also exposes itself to anti-avoidance measures such as thin capitalisation and transfer pricing provisions. The existence of such taxes and anti-avoidance measures in the tax system of a country may deter investors from locating an IHC in such country. Exchange control regulations could also adversely affect the ability of the IHC to perform its functions effectively, as their purpose is to restrict the movement of capital out of the country. The South African legal system contains all these taxes and anti-avoidance measures as well as exchange control provisions. However, it also contains tax instruments that alleviate the tax burden on an investor using an IHC such as the participation exemption, advance tax rulings and a network of tax treaties. Against this background this thesis analyses the South African corporate tax system to determine whether it is suitable for locating an IHC. In the analysis, a comparative study is done of the tax systems of two of the most effective IHC host countries, namely the Netherlands and Mauritius. In addition, a brief discussion of the special features contained in the tax systems of Belgium, Ireland and the United Kingdom outlines why these jurisdictions are not necessarily successful in attracting IHCs. The thesis also discusses harmful tax practices and the attitude of the international community towards countries that engage in harmful tax competition in order to determine the limits to which a country should use the tax system to attract investment. Finally, the thesis makes recommendations as to what adjustments could be made in order to enhance the suitability of South Africa to host an IHC. The thesis recommends a special dispensation as regards corporate income tax and exchange control that would apply to wholly-owned South African companies that own foreign subsidiary shares and loans that consist of 80% of the gross asset total of these companies.
Keywords: Intermediary Holding Company; South Africa; Tax; Taxation

On the Development of West African Accounting System - Moussa, Boka (International Journal of Business and Management, 2010)
The authorities of the West African Economic and Monetary Union UEMOA fully understand that accounting plays the significant role in the process of economic development and regional integration in the member states. They decided to establish a common new accounting system, called West African Accounting System (SYSCOA). The accounting system has been developed on the initiative of the Central Bank of West African States
Number: 5

Impact of Macro and Micro Governance Structures on Earnings Management - Houqe, Muhammad Nurul (Victoria University of Wellington, 2010)
This study examines the macro and micro level determinants of the quality of reported earnings. The prior literature suggests that both micro and macro variables impact on discretionary accruals choice in managing earnings. However, most of the studies on earnings management have been single country studies that have focussed only on micro variables as all firms within the samples examined have been subject to the same interplay of macro economic, legal, cultural and institutional frameworks. This study addresses this gap in the literature by using a sample of 156,906 firm year observations from 63 countries over the period 1998-2007 to examine the role of thirteen micro and macro variables in determining earnings quality. The macro variables studied include legal enforcement, political system, and control of corruption, culture and adoption of IFRS. Earnings management is estimated using the modified Jones model (Dechow et al. 1995) in a cross section (DeFond and Jiambalvo 1994; Francis et al. 1998). The results of the study indicate that macro and micro level variables have a strong impact on earnings management behaviour and thus earnings quality. The limits imposed by a country's legal, cultural and institutional setting on managerial discretionary accruals choices, strongly impact the quality of reported earnings. Future research on earnings management should therefore control both micro and macro level variables.
Keywords: Earnings management; Macro governance; Micro governance